Comparison of C - Reactive Protein and Lipid Profile in Obese Poly Cystic Ovary Syndrome Women and Normal Women of the Reproductive Age Group – A Prospective Case-Controlled Trial: Life Sciences-CRP and Lipid in Obese PCO - R, Dr. Revathi; Rajagopalan, Dr. Balaji; Dr. Swetha; Velu, Dr. V. Kuzhandai (International Journal of Life Science and Pharma Research, 2022)
Serum (C Reactive Protein) CRP is a good predictor of vascular events and has been linked to polycystic ovarian syndrome (PCOS). The increased CRP may be an early marker of upcoming atherosclerotic diseases like coronary artery disease and stroke. To identify the disease of PCOS and its interrelation with increased CRP may work as a clue for its disease progression. The purpose of this study is to evaluate the high-sensitivity C- reactive protein, which is a characteristic of individuals with PCOS of reproductive age. The sample size for this prospective randomized study was 200 people, divided into two equal groups (with or without PCOS). This study included 100 obese women with the polycystic ovarian syndrome and 100 matched controls. These women’s blood samples were tested for serum lipid profile and hsCRP.. The demographic variables were similar between the groups. Our findings revealed that patients with PCOS had high LDL and triglyceride levels. HDL levels were extremely low. This indicates a poor lipid profile in PCOS patients. (The p-value is 0.001). The hs CRP was 9.3 mg compared to 2.9 mg in the control group. According to our findings, hs CRP may provide information about the presence of the disease. As a result, more research is needed to explain the potential role of C-reactive protein in the disease incidence and progression of polycystic ovarian syndrome. Even though there are a lot of studies linking these two, we have done for Hs CRP and PCOS. The sample size is on the higher side in our study.